oMEGACat. V. Helium Enrichment in ω Centauri as a Function of Metallicity - C. Clontz; A. C. Seth; Z. Wang; S. O. Souza; M. Häberle; M. S. Nitschai; N. Neumayer; M. Latour; A. P. Milone; A. Feldmeier-Krause; N. Kacharov; M. Libralato; et al. (The Astrophysical Journal)
Constraining the helium enhancement in stars is critical for understanding the formation mechanisms of multiple populations in star clusters. However, measuring helium variations for many stars within a cluster remains observationally challenging. We use Hubble Space Telescope photometry combined with MUSE spectroscopic data for over 7200 red giant branch stars in ω Cen to measure helium differences between distinct groups of stars as a function of metallicity, separating the impact of helium enhancements from other abundance variations on the pseudo-color (chromosome) diagram. Our results show that stars at all metallicities have subpopulations with significant helium enhancement (Δ Y _min ≳ 0.11). We find a rapid increase in helium enhancement across low metallicities ([Fe/H] ≃ −2.05 to [Fe/H] ≃ −1.92), with this enhancement leveling out at Δ Y = 0.15 at higher metallicities. The fraction of helium-enhanced stars steadily increases with metallicity from 10% at [Fe/H] ≃ −2.04 to over 90% at [Fe/H] ≃ −1.04. From these measurements, we calculate the total mass in helium produced over the cluster’s lifetime, finding ${M}_{{{\rm{He}}}_{{\rm{tot}}}}\sim 2.7× 1{0}^{5}{M}_{\odot }$ . This study is the first to examine helium enhancement across the full range of metallicities in ω Cen, providing new insight into its formation history and additional constraints on enrichment mechanisms.